Th1 cytokines are more effective than Th2 cytokines at licensing anti‐tumour functions in CD40‐activated human macrophages in vitro - Luheshi, Nadia; Davies, Gareth; Poon, Edmund; Wiggins, Kimberley; McCourt, Matthew; Legg, James (European journal of immunology, 2014)
CD40 agonists are showing activity in early clinical trials in patients with advanced cancer. In animal models, CD40 agonists synergise with T‐cell‐activating therapies to inhibit tumour growth by driving tumour macrophage repolarisation from an immunosuppressive to a Th1 immunostimulatory, tumouricidal phenotype. We therefore tested the hypothesis that T‐cell‐derived cytokines license anti‐tumour functions in CD40‐activated human macrophages. CD40 ligand (CD40L) alone activated macrophages to produce immunosuppressive IL‐10, in a similar fashion to bacterial LPS, but failed to promote anti‐tumour functions. The Th1 cytokine IFN‐γ optimally licensed CD40L‐induced macrophage anti‐tumour functions, inducing a switch from IL‐10 to IL‐12p70 production, promoting macrophage‐mediated Th1 T‐cell skewing and enhancing tumouricidal activity. We found that even the Th2 cytokines IL‐4 and IL‐13 promoted IL‐12p70 production (albeit without inhibiting IL‐10 production) and enhanced Th1 T‐cell skewing by CD40L‐activated macrophages. However, IL‐4 and IL‐13 did not enhance tumouricidal activity in CD40L‐activated macrophages. Thus, while both Th1 and Th2 cytokines biased macrophages to a Th1 immunostimulatory phenotype, only Th1 cytokines promoted tumouricidal activity in CD40L‐activated macrophages. The presence of tumour‐infiltrating Th1 or Th2 cells might therefore be predictive for patient response to CD40 agonism.